1998
DOI: 10.1038/26450
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic nitrogen reduction on the early Earth

Abstract: The production of organic precursors to life depends critically on the form of the reactants. In particular, an environment dominated by N2 is far less efficient in synthesizing nitrogen-bearing organics than a reducing environment rich in ammonia. Relatively reducing lithospheric conditions on the early Earth have been presumed to favour the generation of an ammonia-rich atmosphere, but this hypothesis has not been studied experimentally. Here we demonstrate mineral-catalysed reduction of N2, NO2- and NO3- to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(153 citation statements)
references
References 22 publications
1
149
0
3
Order By: Relevance
“…Both reactions can be catalyzed by chemolithoautotrophic microbes over a wide range of temperatures, but the reduction to NH 4 + seems to be less common (Weber et al, 2006). Under ambient temperatures, microbial catalysis greatly accelerates nitrite and nitrate reduction (Weber et al, 2001), but it could occur abiotically under hydrothermal conditions (Brandes et al, 1998;Summers and Chang, 1993). As discussed in Section 5.1, this pathway could have lessened the supply of lightning-derived NO x to the earliest biosphere or prebiotic reaction networks, because a significant fraction of NO x would likely have been returned to the atmosphere as N 2 gas instead of being converted into the more bioavailable form NH 4 + .…”
Section: Effects Of Ferruginous Conditions On the Nitrogen Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…Both reactions can be catalyzed by chemolithoautotrophic microbes over a wide range of temperatures, but the reduction to NH 4 + seems to be less common (Weber et al, 2006). Under ambient temperatures, microbial catalysis greatly accelerates nitrite and nitrate reduction (Weber et al, 2001), but it could occur abiotically under hydrothermal conditions (Brandes et al, 1998;Summers and Chang, 1993). As discussed in Section 5.1, this pathway could have lessened the supply of lightning-derived NO x to the earliest biosphere or prebiotic reaction networks, because a significant fraction of NO x would likely have been returned to the atmosphere as N 2 gas instead of being converted into the more bioavailable form NH 4 + .…”
Section: Effects Of Ferruginous Conditions On the Nitrogen Cyclementioning
confidence: 99%
“…Rates of up to 10 12 mol N/yr may have been achieved under high pCH 4 (1000ppmv) and <1% pCO 2 favoring the production of HCN later in the Archean (Tian et al, 2011;Zahnle, 1986), but pCH 4 would probably have been low in the Hadean under prebiotic conditions prior to the origin of methanogenic microbes, lowering this flux to 10 9 mol N/yr. Lightning and volcanism both generate NO x species which could have been reduced abiotically into the more bioavailable NH 4 + in hydrothermal vents, catalyzed by sulfide minerals or native metals (Brandes et al, 1998;Singireddy et al, 2012;Smirnov et al, 2008;Summers and Chang, 1993), provided that the reduction did not stop at N 2 (Section 2.3). Reduction of NO x to N 2 may have greatly diminished the abiotic supply of fixed nitrogen to prebiotic reactions and the earliest biosphere.…”
Section: Was There a Significant Source Of Abiotically Fixed Nitrogen?mentioning
confidence: 99%
See 1 more Smart Citation
“…The driving forces of the overall reaction are the oxidation of iron sulfide to iron disulfide and the formation of hydrogen from H 2 S. [6] Hazen et al reported a nitrogen reduction at temperatures between 300 and 800 8C and pressures of 0.1 to 0.4 GPa. [7] The molecular hydrogen necessary for this reduction was obtained from H 2 O by using the magnetite/formic acid/metallic iron system as a reductant. Hazen et al consider this a typical reaction, which could have taken place under conditions prevailing on the primordial earth.…”
mentioning
confidence: 99%
“…Un grupo de investigadores del Carnegie Institution of Washington, mediante experimentos a temperaturas de 300-800°C y presiones de 0.1-0.4 GPa, representativas de los sistemas hidrotermales submarinos, mostró que el N 2 procedente de la atmósfera pudo haber sufrido una reducción a NH 3 dentro de estos sistemas por efecto de la acción catalítica de los minerales hidrotermales (Brandes et al, 1998). Por otra parte, ha sido considerado que, mediante este mecanismo de intercambio con la atmósfera, el amoníaco hidrotermal, además de su rol esencial en la síntesis orgánica, podría haberse sumado al amoníaco atmosférico para resolver la llamada "paradoja del sol joven", como fue propuesto por Sagan y Chyba (1997).…”
Section: Océanosunclassified